Ultrastructural Changes in Clinical and Microbiota Isolates of Klebsiella pneumoniae Carriers of Genes blaSHV, blaTEM, blaCTX-M, or blaKPC When Subject to β-Lactam Antibiotics - Dyana Leal Veras; Ana Catarina de Souza Lopes; Grasielle Vaz da Silva; Gabriel Gazzoni Araújo Gonçalves; Catarina Fernandes de Freitas; Fernanda Cristina Gomes de Lima; Maria Amélia Vieira Maciel; Ana Paula Sampaio Feitosa; Luiz Carlos Alves; Fábio André Brayner (The Scientific World Journal)
The aim of this study was to characterize the ultrastructural effects caused by β-lactam antibiotics in Klebsiella pneumoniae isolates. Three K. pneumoniae clinical isolates were selected for the study with resistance profiles for third-generation cephalosporins, aztreonam, and/or imipenem and with different resistance genes for extended-spectrum β-lactamases (ESBL) or Klebsiella pneumoniae carbapenemase (KPC). Two K. pneumoniae isolates obtained from the microbiota, which were both resistant to amoxicillin and ampicillin, were also analyzed. In accordance with the susceptibility profile, the clinical isolates were subjected to subminimum inhibitory concentrations (sub-MICs) of cefotaxime, ceftazidime, aztreonam, and imipenem and the isolates from the microbiota to ampicillin and amoxicillin, for analysis by means of scanning and transmission electron microscopy. The K. pneumoniae isolates showed different morphological and ultrastructural changes after subjection to β-lactams tested at different concentrations, such as cell filamentation, loss of cytoplasmic material, and deformation of dividing septa. Our results demonstrate that K. pneumoniae isolates harboring different genes that encode for β-lactamases show cell alterations when subjected to different β-lactam antibiotics, thus suggesting that they possess residual activity in vitro, despite the phenotypic resistance presented in the isolates analyzed.